Strategic Factors and Business Environment Potential Causes of Non-Sustainability of Family Business in Semarang and The Surrounding - Arie Sulistiono; Budi Widianarko; Berta Bekti Retnowati (Green Publisher Indonesia, 2023)
In order to fulfill the goals and strategic objectives of the company that was founded, every company or corporation is expected to have sustainability in its business, including family companies which are the largest part of the ranks of companies in general. The biggest part of the line of companies because in general companies generally start from family businesses. This research is part of the main research dissertation that aims to examine the Construction of a Theory-Based Family Company Sustainability Model which researchers are currently completing. The theory of Corporate Sustainability is one of the filters and at the same time an inspiration for companies to survive or not on their way. This study uses qualitative research methods to reveal facts and realities about family businesses. With the process of collecting data systematically, validating data by triangulation, data processing to concluding research data based on the relationship between the propositions revealed. The results of this study will present some of the conclusions from the main research based on accurate and relevant data to answer the question of what strategic factors and what business environment factors cause a family business to become unsustainable. So that the research findings become a recommendation on how to anticipate and plan a family business to be more lasting and sustainable.